Visualizing the high curvature regions of post-mitotic nascent nuclear envelope membrane - Lu, Lei (2013)
We previously reported that mitotic endoplasmic reticulum (ER) membrane cisternae or sheets directly assemble mammalian nuclear envelope (NE) at the end of mitosis. In this study, we investigated the dynamics of the high curvature regions of partially assembled nuclear envelope membrane using reticulon4a as a probe. We found that, after sorting out reticulon4a from the nascent NE membrane sheets, reticulon4a is specifically localized to the leading edges. Our 3D time lapse images suggested that ER tubules could be incompetent in assembling the NE membrane. Our findings suggest a possible role of reticulons at the leading edges during the NE re-assembly and provide further evidences that the mitotic assembly of NE is by ER cisternae rather than tubules.